Surgical management of endometriosis: review of the literature - Simavičius, Andrius; Bogužienė, Emilija; Kupčiūnaitė, Rasa; Černauskis, Karolis (Lietuvos chirurgija, 2015)
Endometriosis is a common disease of reproductive age women, causing not only pain but also infertility. Surgery is one of the most important steps of endometriosis treatment. Correct surgical treatment not only reduces the symptoms, but also improves the pregnancy rate with infertility. Advances in laparoscopic surgery have made the surgical management of endometriosis an effective treatment that offers advantages over medical therapy. Endometriosis can be understood as three different forms of the disease: peritoneal disease, ovarian disease, deep infiltrating rectovaginal endometriosis. The majority of gynaecologists readily perform laparoscopic ablation of superficial disease. Excision of deeper disease and management of rectovaginal disease require more expertise and should be managed in tertiary centres. Surgical treatment of endometriosis can be conservative or definitive, when both ovaries are removed. When endometriosis is identified at laparoscopy, clinicians are recommended to surgically treat endometriosis and remove all visible lesions. The aim of this article is to understand the role of surgery in the management of endometriosis and to be aware of the best available evidence on the proper surgery of endometriosis.
Keywords: endometriosis; endometrioma; deep infiltrating endometriosis; ablation; excision; rectovaginal septum; laparoscopy